Effects of traditional Chinese exercise on lung function and mental health in patients with COPD: a systematic review and meta-analysis - Liu, Shuning; Xu, Debin (Frontiers in Public Health, 2025)
ObjectiveDespite their widespread use in the management of chronic obstructive pulmonary disease (COPD), pharmacological treatments often demonstrate limited efficacy in alleviating symptoms such as dyspnea and psychological pressure. These limitations highlight the need for complementary nonpharmacological interventions. This study aimed to evaluate the efficacy of traditional Chinese exercise (TCE) in improving lung function and mental health among patients with COPD.MethodsWe conducted a comprehensive search across several databases: CNKI (1979–2024), Wanfang (1998–2024), PubMed (1966–2024), the Cochrane Library (1999–2024), and Web of Science (1961–2024), up to September 2024, to gather all randomized controlled trials (RCTs) studies that evaluated the effects of TCE as the primary intervention for patients with COPD. The results were analyzed and presented using Review Manager 5.4 software, ensuring a systematic approach to data interpretation and visualization.Results67 studies were included and encompassing 5,475 patients. The meta-analysis demonstrated that TCE significantly improved various outcomes in COPD patients, including FEV1 [MD = 0.28, 95% CI (0.23, 0.33), p < 0.001], FEV1% [MD = 5.53, 95% CI (4.41, 6.65), p < 0.001], FVC [MD = 0.31, 95% CI (0.29, 0.34), p < 0.001], FEV1/FVC (%) [MD = 6.00, 95% CI (4.27, 7.73), p < 0.001], the 6MWT [MD = 42.14, 95% CI (36.54, 47.73), p < 0.001], CAT [MD = −4.20, 95% CI (−4.74, −3.66), p < 0.001], anxiety [MD = −1.26, 95% CI (−1.64, −0.89), p < 0.001], and depression [MD = −1.26, 95% CI (−1.59, −0.94), p < 0.001].ConclusionTCE significantly improved lung function and alleviated anxiety and depression in COPD patients. This study not only highlights the value of TCE as a nonpharmacological intervention but also offers new directions for psychological management, warranting broader implementation.Systematic review registrationCRD42024586079, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024586079.